Impact of Organizational Culture on Entrepreneurial Behavior with the Mediating Role of Social Capital: Path Analysis - Sana Shaaban; Mohammad Reza Mohammad Khani; Ahad Alizade; Zahra Mirhajian; Zeinab Momeni; Sima Rafiei (Shahid Sadoughi University of Medical Sciences, 2022)
Background: Organizational culture can affect the levels of entrepreneurship and innovation through identifying the social capital dimensions and enhance the ability of staff to accept challenges. This study aimed to examine the impact of organizational culture on entrepreneurial behavior with the mediating role of social capital among the staff working in Qazvin University of Medical Sciences. Methods: This was an cross-sectional analytical study conducted among the staff of Qazvin University of Medical Sciences in 2020. Sample size was calculated by Cochran formula considering type I error and the accuracy of 5 % and was equal to 122 individuals. Addressing sample attrition, the final size considered to be 143 people by calculating 15 % increase. The standard questionnaires of entrepreneurial behavior were applied to collect the data. Descriptive statistical tests were used in order to analyze the data; moreover, correlation coefficients were applied to examine the relationship between the main variables of the study. Furthermore, the Structural Equation Analysis (SEM) test was used by LISREL and SPSS software to test the research hypotheses. Results: The estimated coefficient reported for the relationship between organizational culture and entrepreneurial behavior was 23 %; while it was reported to be 12 % for the relationship between social capital and behavior. Furthermore, the hypothesis that social capital mediates the relationship between organizational culture and entrepreneurial behavior was confirmed (T statistic = 3.310, Std. Error = 0.110, P-value < 0.001 ). Conclusion: The results of the present study necessitate further attention to university environments and higher education institutions for creating an entrepreneurship culture by establishing a flexible structure with participatory and supportive management in order to empower human resources and encourage them to promote social capital. Holding discussion sessions with staff and using their pure ideas and avoiding the implementation of strict regulations in addition to creating a participatory atmosphere can play important role in this regard.